Eu sou o pão da vida! Uma controvérsia em Jo 6,22-59 - Santos, Ana Pinheiro dos (2011)
Christianity to establish itself as a religion around the table, in the Eucharist had a decent meal, as a symbol and a position in the face of reality. Address the meaning of food in the pericope of John 6,22-59 constitutes a milestone for Christianity that lets you see how this issue as related to issues of daily life, it has added symbols, images and concepts to reframe food.